Association of Magnesium Depletion Score With Cardiovascular Disease and Its Association With Longitudinal Mortality in Patients With Cardiovascular Disease - Ye, Liu; Zhang, Cheng; Duan, Qin; Shao, Yue; Zhou, Jianzhong (Journal of the American Heart Association, 2023)
Background Dietary magnesium and serum magnesium play an important part in cardiovascular disease (CVD). However, the association between magnesium depletion score (MDS) and CVD development and prognosis remains unclear. This analysis examines the cross-sectional relationship between MDS and CVD, and the longitudinal association between MDS and all-cause and CVD mortality in individuals with CVD. Methods and Results In all, 42 711 individuals were selected from the National Health and Nutrition Examination Survey, including 5015 subjects with CVD. The association between MDS and total and individual CVDs was examined using the survey-weighted multiple logistic regression analysis. Among 5011 patients with CVD, 2285 and 927 participants were recorded with all-cause and CVD deaths, respectively. We applied survey-weighted Cox proportional hazards regression analyses to investigate the impact of MDS on the mortality of individuals with CVD. The CVD group had higher MDS levels than the non-CVD groups. After controlling all confounding factors, individuals with MDS of 2 and ≥3 had higher odds of total CVD and specific CVD than those with MDS of 0. Besides, each 1-unit increase in MDS was strongly related to the risk of total CVD and specific CVD. The relationship between MDS and total CVD was stable and significant in all subgroups. The fully adjusted Cox regression model indicated that high MDS, irrespective of MDS as a categorical or continuous variable, was significantly associated with an elevated risk of all-cause and CVD deaths. Conclusions MDS is a vital risk factor for the prevalence and mortality of individuals with CVD.Background Dietary magnesium and serum magnesium play an important part in cardiovascular disease (CVD). However, the association between magnesium depletion score (MDS) and CVD development and prognosis remains unclear. This analysis examines the cross-sectional relationship between MDS and CVD, and the longitudinal association between MDS and all-cause and CVD mortality in individuals with CVD. Methods and Results In all, 42 711 individuals were selected from the National Health and Nutrition Examination Survey, including 5015 subjects with CVD. The association between MDS and total and individual CVDs was examined using the survey-weighted multiple logistic regression analysis. Among 5011 patients with CVD, 2285 and 927 participants were recorded with all-cause and CVD deaths, respectively. We applied survey-weighted Cox proportional hazards regression analyses to investigate the impact of MDS on the mortality of individuals with CVD. The CVD group had higher MDS levels than the non-CVD groups. After controlling all confounding factors, individuals with MDS of 2 and ≥3 had higher odds of total CVD and specific CVD than those with MDS of 0. Besides, each 1-unit increase in MDS was strongly related to the risk of total CVD and specific CVD. The relationship between MDS and total CVD was stable and significant in all subgroups. The fully adjusted Cox regression model indicated that high MDS, irrespective of MDS as a categorical or continuous variable, was significantly associated with an elevated risk of all-cause and CVD deaths. Conclusions MDS is a vital risk factor for the prevalence and mortality of individuals with CVD.